Prehistoric maritime adaptations of the circumpolar zone - Fitzhugh, William W., 1943- (World anthropology., 1975)
Papers examining the anthropology and archaeology of early cultures in Scandinavia, the North Pacific and Bering Sea, and the northwest Atlantic, with comparative studies of various aspects.